1983
DOI: 10.1017/s0022112083001512
|View full text |Cite
|
Sign up to set email alerts
|

Instabilities of dynamic thermocapillary liquid layers. Part 1. Convective instabilities

Abstract: A planar liquid layer is bounded below by a rigid plate and above by an interface with a passive gas. A steady shear flow is set up by imposing a temperature gradient along the layer and driving the motion by thermocapillarity. This dynamic state is susceptible to two types of thermal-convective instabilities: (i) stationary longitudinal rolls, which involve the classical Marangoni instability studied by Pearson; and (ii) unsteady hydrothermal waves, which involve a new mechanism of instability deriving its en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

71
455
2
5

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 629 publications
(533 citation statements)
references
References 21 publications
71
455
2
5
Order By: Relevance
“…The existence of hydrothermal waves in a fluid layer subjected to a horizontal temperature gradient has been predicted on the basis of a linear stability analysis by Smith and Davis [23], and studied numerically in conditions close to our experimental situation by Mercier and Normand [40]. Hydrothermal waves have been detected and characterized in several experiments [13,18,24,25,41].…”
Section: Hydrothermal Wavesmentioning
confidence: 70%
See 1 more Smart Citation
“…The existence of hydrothermal waves in a fluid layer subjected to a horizontal temperature gradient has been predicted on the basis of a linear stability analysis by Smith and Davis [23], and studied numerically in conditions close to our experimental situation by Mercier and Normand [40]. Hydrothermal waves have been detected and characterized in several experiments [13,18,24,25,41].…”
Section: Hydrothermal Wavesmentioning
confidence: 70%
“…[11,12] Among these different waves systems, thermocapillary flows and in particular hydrothermal waves [13][14][15][16][17][18] or hot wire waves [19][20][21][22] appear as a very simple tool, owing to their supercritical bifurcation. They correspond to the first instability of a thin liquid layer with a free surface subjected to a horizontal temperature gradient [23]. Different experimental configurations have been used to study those traveling waves: rectangular cells with different aspect ratios [13,24,25,18,15], annular cells [26,14], cylindrical cells [27,17] and linear hot wire under the surface of a liquid [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…the thermal Couette flow. Particula rly, Smith and Davis [4] found that for this linear base flow, when it was subjected to spanwise disturbance s, convection may occur in the form of stationary longitudina l rolls, or in the form of hydrothe rmal waves. The hydrothermal wave only occurs when the Prandtl number is small.…”
Section: Introductionmentioning
confidence: 95%
“…Linear stability analysis of Pearson predicts the threshold value of Marango ni number, Ma = 79.6, which coincides with experiments. Smith and Davis [4,5] and Davis [6] considered thermocapillary instabilities in a single layer system with a non-deformabl e interface. Sen and Davis [7] studied steady thermocapi llary flows in two-dimensi onal slots.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation